Accelerated aging associated with computerized analysis (Vigor-S) to evaluate the vigor of soybean seeds - Assunção, Cleverton Timóteo de; Silva, Martha Freire da; Leal, José Henrique Siqueiras (Revista de Ciências Agroveterinárias, 2025)
Tests used to assess the physiological quality of seeds need improvement to optimize the use of seeds, resources, and labor. The development of new tests and/or adjustments to existing ones can allow better screening of vigor between lots and be more predictive of seed performance in the field, especially for new cultivars. Thus, the aim of this study was to verify the effectiveness of a new methodology for assessing the physiological quality of soybean seeds. This methodology is based on the accelerated aging test associated with computerized analysis of the images of seedlings from aged seeds. For this purpose, soybean seeds from three cultivars, and four lots of each cultivar, were used. The physiological quality of the seeds was characterized using germination and vigor tests. Subsequently, the proposed new methodology was applied, where the seeds were aged at 41 °C and 100% relative humidity for periods of 0, 24, 48, and 72 hours, followed by computerized image analysis of the seedlings from the aged seeds. It was observed that accelerated aging, using a temperature of 41 °C, and relative humidity of 100% for 72 hours, followed by computerized image analysis of seedlings, is a potential new methodology to assess the physiological quality of soybean seeds.